COMPARATIVE INFRARED SPECTROSCOPIC STUDY OF NATURAL CA-AMPHIBOLES - Theodosoglou, E.; Koroneos, A.; Paraskevopoulos, K. M.; Christofides, G.; Papadopoulou, L.; Zorba, T. (Bulletin of the Geological Society of Greece, 2007)
Powder IR spectra of natural Ca-amphiboles were studied in the spectral range 4000 to 400 cm'1. The examined samples are: actinolite, tremolite, Mg-hornblende and pargasite. According to their spectra all the minerals of the four species present common features at 3658-3660, 919, 683-687, 661-668, 505-513, 457-464 and 419 cm . Additionally to these bands, the spectra of the actinolites, tremolites and Mghornblendes present common characteristics at 3673, 1094-1098, 989-998, 951, 752-758 and 441-449 cm'1. Moreover, six absorption bands are shown in the spectra of the pargasites at 3690, 981-984, 931, 805-811, 734 and 696-698 cm'1, in addition to the common bands appeared in all Ca-amphiboles, which do not appear in the spectra of the actinolites, tremolites and Mg-hornblendes. The spectra of pargasites are remarkably different from the spectra of the other three mineral species. These discrepancies could be attributed to differences in the structure of pargasites relative to the other three species as well as to the occupancy of the A site especially with Na+.